Risk factors for non-communicable diseases in Afghanistan: insights of the nationwide population-based survey in 2018 - Omid Dadras; Muhammad Haroon Stanikzai; Massoma Jafari; Essa Tawfiq (BMC, 2024)
Abstract Background Noncommunicable diseases (NCDs) account for a substantial number of deaths in Afghanistan. Understanding the prevalence and correlates of major NCD risk factors could provide a benchmark for future public health policies and programs to prevent and control NCDs. Therefore, this study aimed to examine the prevalence and correlates of NCD risk factors among adults aged 18-69 years in Afghanistan. Methods We used data from the Afghanistan STEPS Survey 2018. The study population were 3650 (1896 males and 1754 females) adults aged 18-69 years sampled from all 34 provinces through a multistage cluster sampling process. Information on behavioural and biological risk factors was collected. We used STATA (version 18.0) for data analysis. Results Of the total participants, 42.8% were overweight or obese, 8.6% were current smokers, 26.9% had insufficient physical activities, 82.6% had low consumption of fruits and vegetables, and only 0.5% had ever consumed alcohol. Approximately 15% of participants had a high salt intake, while 25% and 8% had elevated blood pressure and blood glucose levels, respectively. Similarly, around 18% had elevated total cholesterol. The study revealed a lower prevalence of current smoking among females [AOR = 0.17, 95%CI (0.09-0.30)] compared with males, but a higher prevalence in those who had higher education levels [1.95 (1.13-3.36)] compared with those with no formal education. Insufficient physical activity was higher in participants aged 45-69 years [1.96 (1.39-2.76)], females [4.21 (1.98-8.84)], and urban residents [2.38 (1.46-3.88)] but lower in those with higher education levels [0.60 (0.37-0.95)]. Participants in the 25th to 75th wealth percentiles had higher odds of low fruit and vegetable consumption [2.11 (1.39-3.21)], while those in the > 75th wealth percentile had lower odds of high salt intake [0.63 (0.41-0.98)]. Being overweight/obese was more prevalent in participants aged 45-69 years [1.47 (1.03-2.11)], females [1.42 (0.99-2.01)], currently married [3.56 (2.42-5.21)] or ever married [5.28 (2.76-10.11)], and urban residents [1.39 (1.04-1.86)]. Similarly, high waist circumference was more prevalent in participants aged 45-69 years [1.86 (1.21-2.86)], females [5.91 (4.36-8.00)], those being currently married [4.82 (3.12-7.46)], and those being in 25th to 75th wealth percentile [1.76 (1.27-2.43)]. A high prevalence of elevated blood pressure was observed in participants aged 45-69 years [3.60 (2.44-5.31)] and currently married [2.31 (1.24-4.31)] or ever married [6.13 (2.71-13.8)] participants. Elevated blood glucose was more prevalent in older adults ([1.92 (1.09-3.39)] for 45-69 and [3.45 (2.44-5.31)] for 30-44 years), urban residents [2.01 (1.33-3.03)], and ever-married participants [4.89 (1.48-16.2)]. A higher prevalence of elevated cholesterol was observed in females [2.68 (1.49-4.82)] and those currently married [2.57 (1.17-5.63)] or ever married [4.24 (1.31-13.73)]. Conclusion This study used up-to-date available data from a nationally representative sample and identified the prevalence of NCDs and associated risk factors in Afghanistan. Our findings have the potential to inform and influence health policies by identifying people at high risk of developing NCDs and can assist policymakers, health managers, and clinicians to design and implement targeted health interventions.